Exploring the Effectiveness of Babad Pasirluhur Story to Teach Past Simple and Students’ Perspective on Its Usage - Insif, Ahmad Iqwamul; Aniuranti, Asfi; Wulandari, Yasinta (Educalitra: English Education, Linguistics, and Literature Journal, 2022)
The purposes of this study were to investigate the effectiveness of a local story entitled Babad Pasirluhur for teaching past simple and students’ voices on its usage. Therefore, the method employed was quasi-experimental research, and the instruments used were a multiple-choice item test and a closed questionnaire. The result revealed that Babad Pasirluhur story was effective to teach past simple because the value of Mann Whitney test result (97.5) was lower than Mann Whitney table (324). The significance level was 0.05. Furthermore, the result of the questionnaire showed that most of the students had positive responses toward Babad Pasirluhur. Overall, a local story entitled Babad Pasirluhur was effective to teach past simple, and the students mostly gave positive responses to the story.